In vitro impact of ethanolic extract of Bryonia laciniosa seed on Gir bull spermatozoa: a comprehensive evaluation through transcriptome profiling - Italiya, Jignesh; Panchal, Ketankumar J.; Jakhesara, Subhash J.; Joshi, Chaitanya G.; Koringa, Prakash G. (Frontiers in Veterinary Science, 2024)
This study examines the in vitro impact of an ethanolic extract derived from Bryonia laciniosa seeds on the Gir bull (Bos indicus) spermatozoa. The objective is to thoroughly assess the effects of the seed extract on the physiological parameters of bull spermatozoa, followed by evaluating its effects on X and Y-bearing spermatozoa and its impact on gene expression through transcriptome profiling.For this study, one Gir bull was selected, and fifteen ejaculates were collected at one-week time intervals. Sperm cells were isolated from each ejaculate and incubated with varying concentrations of the ethanolic extract. The physiological parameters of the spermatozoa were assessed using Computer Assisted Semen Analysis (CASA) and compared with control groups to evaluate the extract's effects on sperm quality and motility. At a concentration of 18 mg/mL Bryonia laciniosa extract, we noticed a statistically significant 16.4% increase in sperm motility (p = 0.0065). In order to understand the specific effect on X and Y-bearing spermatozoa, motile and non-motile sperm separated by glass wool column method and further evaluated for quantification of X and Y-bearing sperm in all samples by ddPCR. To understand the effect of Bryonia laciniosa extract on spermatozoa at the molecular level, whole transcriptome profiling was carried out using Illumina MiSeq.Transcriptome profiling revealed 81 genes that were expressed differently between the group treated with the extract and the control group. The current investigation revealed an increase in the expression of TLX1, CRYGB, KLF13, and ZAR1 transcripts, which play a role in embryonic development. In addition, several genes have been identified that are involved in sperm motility, such GSK3B, LAPRS, MAPK1, CAMK2B, and AQP7. The findings exhibited the therapeutic effectiveness of Bryonia laciniosa seeds in augmenting fertility through a synergistic blend of activities, including enhanced sperm motility and positive influence on embryogenesis.